Hubungan Pengetahuan Tentang Bahan Makanan Sumber Lemak Dengan Tingkat Konsumsi Lemak Dan Kadar Kolesterol Total Pasien Hiperkolesterolemia Anggota Persatuan Diabetisi (PERSADIA) Mataram - Wahidatul Laeni Sa’adah; Aladhiana Cahyaningrum; NiKetut Sri Sulendri; Fifi Luthfiyah (Poltekkes Kemenkes Mataram, 2018)
Background. Hypercholesterolemia is increased levels of total cholesterol in the blood that exceeds normal levels (more than 200 mg/dl). According to the Health Survey Households in 2004, the prevalence of Hypercholesterolemia in Indonesia at age 25-34 years amounting to 9.3%, whereas at ages 55-64 years amounted to 15.5%. Uncontrolled consumption of fats is one of the causes of Hypercholesterolemia. Knowledge of nutrition is a very important factor in determining a person's behaviorand attitude towards food, the higher the nutritional knowledge then it would increasingly take into account the type and amount of food consumed by a person. Research Methods. This research is Observational Analytic study, in terms of time is Crossectional study objectives, are all members of the Persadia Mataram that active following activities in Mataram Persadia meets the criteria, the research was obtained on the number of samples 34 people. To know the relation of free variables and bound variables was done using test bivariat analysis of rank spearman with the level of significance of 5%. Research Result. The sample in this research 70.6% aged >60 years, 76.5% occur in women, 38.2% work as pensioners, 55.9% college educated, 67.6% hypercholesterolemia diagnosed with diabetes complications, 58.8% of the sample of cholesterol-lowering drugs and 35.2% with diagnosed 5-10 years old. Based on the results of statistical tests known value of P are respectively 0.233 and 0.591 (P> 0.05), meaning that there is no relationship of knowledge about food sources of fat with fat consumption levels and total cholesterol levels. Conclusion. There is no relationship of knowledge about food sources of fat with fat consumption level, and no fat consumption level of relationship with total cholesterol levels.